Altered processing of visual emotional stimuli in posttraumatic stress disorder: an event-related potential study. Issue 2 (30th August 2015) - Saar-Ashkenazy, Rotem; Shalev, Hadar; Kanthak, Magdalena K.; Guez, Jonathan; Friedman, Alon; Cohen, Jonathan E.
Abstract: Patients with posttraumatic stress disorder (PTSD) display abnormal emotional processing and bias towards emotional content. Most neurophysiological studies in PTSD found higher amplitudes of event-related potentials (ERPs) in response to trauma-related visual content. Here we aimed to characterize brain electrical activity in PTSD subjects in response to non-trauma-related emotion-laden pictures (positive, neutral and negative). A combined behavioral-ERP study was conducted in 14 severe PTSD patients and 14 controls. Response time in PTSD patients was slower compared with that in controls, irrespective to emotional valence. In both PTSD and controls, response time to negative pictures was slower compared with that to neutral or positive pictures. Upon ranking, both control and PTSD subjects similarly discriminated between pictures with different emotional valences. ERP analysis revealed three distinctive components (at 300, 600 and 1000 ms post-stimulus onset) for emotional valence in control subjects. In contrast, PTSD patients displayed a similar brain response across all emotional categories, resembling the response of controls to negative stimuli. We interpret these findings as a brain-circuit response tendency towards negative overgeneralization in PTSD. Highlights: Differential brain emotional response was evident in controls but not in PTSD. Three emotional responsive ERPs were found in controls but not in PTSD. Patient's brain-response to all valences resembled control's for negative stimuli. A general "negative-signature" is evident in PTSD patients. The general "negative-signature" may underlie over-generalization characteristic of PTSD.